LEARNING MODULES FOR TRAINING MUTUAL FUND TO INVESTORS - Vijaya Kittu Manda; Aruna Polisetty (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Financial Education is an essential life skill and is a specialization module in adult education and training. Within the financial education domain, a sub-module would be on financial instruments, such as Mutual Funds. Mutual Funds are small retail investor-friendly investment tools. They are increasingly getting investor interest worldwide because they can provide potential solutions for short- and long-term investing. However, like any other financial/investing topic, teaching mutual fund concepts is challenging because of its unique vocabulary, jargon, and investment processes. The paper highlights broad modules that can be part of a typical mutual fund curriculum. Pedagogical Action Research is used to build the teaching modules focusing on narrativity, pupil's agency, curriculum development, practical theories, and ethics. Findings from this work can help teachers and trainers in the financial domain, mutual fund distributors, asset management companies, and the capital market regulators in building financial products that are easier to understand and invest in by small retail investors.